الشيخ العلامة غلام النصير الشهير ب"جلاسي بابا" بين أعماله الدينية و أعماله الأدبية واللغوية: دراسة تاريخية مقارنة - د. شير على خان; د. ذاكرة جهانتاب (Al Manhal Research Journal, 2025)
The article deals with the literary, linguistic, mystic and spiritual life of a a religious scholar who posseses a unique personality and a God gifted knowledge علم لدني)), who was entitled as “Baba Jilasi” when he was 16 year old. In that early period of his life, his poetic verses in Persian language, Shina language (mother tongue), Arabic and Pushto were recited by the scholars in the sermons of Juma congregation. He neither studied Islamic books in any religious school in Pakistan nor entered in the believing chain of any mystic school. Allah al-Mighty opened his chest for understanding divine messages with his God gifted abilities. A large collection of his poetic and prose works in five languages, is the evidence of religious status as a saint. The article throws light on his religious, linguistics, and literary works with examples from his books with translation and analysis.